Pengaruh Model Pembelajaran Kooperatif Berbasis ASSURE Terhadap Hasil Belajar Matematika Siswa - Ariska Amalia Wulandari; Syahrul Azmi; Tabita Wahyu Triutami; Ketut Sarjana (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This is experimental research. This research aims to examine the effect of cooperative learning based on ASSURE model on mathematic learning outcomes in class XI of MAN 2 Mataram. The population is entire students in class XI MAN 2 Mataram with XI Science-5 as experiment class and XI Science-4 as control class which is decided by cluster random sampling. The experiment class was divided into learning teams based on their learning style. The hypothesis test uses a separated variance t-test. Based on the hypothesis test we got that (1) There is a difference in the average of student’s learning outcomes that cooperative learning based on ASSURE model gets a higher score than direct method learning, and (2) cooperative learning model based on ASSURE takes significant effect on learning outcome that class with this model get higher gain-score category than direct method learning.